How do facilitators most effectively support CAL?: an account of practice of a facilitator's research project. (2nd September 2019) - Scott, Daniel
ABSTRACT: While on my own journey of personal development in action learning facilitation, I conducted a research project in response to the question: How do facilitators most effectively support Critical Action Learning (CAL)? From selecting the topic and establishing the methodology, through to collecting data and analysing the results, this account shares what I learned throughout the process – as both a first-time researcher and a growing advocate of CAL in organisations. The results of the study were not what I expected. Although I had learned action learning facilitation should always be neutral and learner-led, the results raised significant questions for me around the potential use of more structured and directive approaches to better enable CAL to create real change in organisations.